CTIM-18. LUMINOS-101: INITIAL SAFETY AND TOLERABILITY OF PVSRIPO AND PEMBROLIZUMAB COMBINATION THERAPY IN RECURRENT GLIOBLASTOMA. (12th November 2021) - Sloan, Andrew; Buerki, Robin; Landi, Daniel; Desjardins, Annick; Friedman, Allan; Ambady, Prakash; Becker, Kevin; Butowski, Nicholas; Cavaliere, Robert; Curry, William; Ong, Shirley; Vega, Rafael; et al.
Abstract: BACKGROUND: Recurrent glioblastoma (rGBM) is rapidly fatal with current therapies. PVSRIPO is an intratumoral immunotherapy targeting CD155 on antigen-presenting and malignant cells of solid tumors. Preclinically, PVSRIPO treatment leads to systemic, tumor antigen-specific, polyfunctional T-cell–mediated anti-tumor response, predominately driven by type I/III interferons. This inflammatory signature generates anti-tumor immunity and upregulates the programmed death (PD)-1 immune checkpoint in the tumor microenvironment. Preclinical models (including GBM) have shown that PVSRIPO+anti-PD-1/L1 therapy was more efficacious than either agent alone, warranting further investigation. METHODS: Adults with histologically confirmed rGBM (1-2 prior progressions), Karnofsky performance status (KPS) ≥70, and an active, supratentorial, contrast-enhancing lesion (1-5.5 cm), received PVSRIPO (5x10 7 TCID50 ) intratumorally via convection-enhanced delivery (Day 1), followed by 200 mg pembrolizumab IV at week 2, given every 3 weeks for up to 24 months, to evaluate the safety/efficacy of the combination. A safety lead-in period (n=3-6) with a minimum 21–28-day delay before treatment of subsequent patients was planned, with a data safety monitoring board (DSMB) evaluating safety/tolerability prior to expansion (up to N=30). RESULTS: The first 3 patients enrolled (ages 55-60, KPS 90-100) all received PVSRIPO followed by pembrolizumab (1-5 cycles), as planned. At cutoff (26-106 days of follow-up), there were no dose-limiting toxicities, treatment-emergent (TE) serious adverse events (SAE), or TEAEs necessitating a delay in initial/subsequent pembrolizumab treatments. All patients experienced a related TEAE, all grade 1 or 2 in severity. One patient experienced an AE of special interest (peritumoral edema, resulting in headache and hemiparesis), successfully managed with low-dose bevacizumab and corticosteroids. The DSMB unanimously recommended the study proceed without modification. CONCLUSIONS: Intratumoral PVSRIPO+pembrolizumab was reasonably well tolerated, warranting continued investigation of the safety and efficacy of this combination in patients with rGBM.